Graphene-Based Transparent Electrodes for Hybrid Solar Cells - Li, Pengfei; Chen, Caiyun; Zhang, Jie; Li, Shaojuan; Sun, Baoquan; Bao, Qiaoliang (Frontiers in Materials, 2014)
The graphene-based transparent and conductive films were demonstrated to be cost-effective electrodes working in organic-inorganic hybrid Schottky solar cells. Large area graphene films were produced by chemical vapor deposition (CVD) on copper foils and transferred onto glass as transparent electrodes. The hybrid solar cell devices consist of solution processed poly (3, 4-ethlenedioxythiophene): poly (styrenesulfonate) (PEDOT: PSS) which is sandwiched between silicon wafer and graphene electrode. The solar cells based on graphene electrodes, especially those doped with HNO3, has comparable performance to the reference devices using commercial indium tin oxide (ITO). Our work suggests that graphene-based transparent electrode is a promising candidate to replace ITO.